2017
DOI: 10.1111/hae.13383
|View full text |Cite
|
Sign up to set email alerts
|

Mid‐term outcomes and complications of total knee arthroplasty in haemophilic arthropathy: A review of consecutive 131 knees between 2006 and 2015 in a single institute

Abstract: The mid-term results of TKA in haemophilic arthropathy were satisfactory in pain relief, improved function and decreased flexion contracture. Bleeding and PJI continue to be major concerns for TKA in haemophilic arthropathy, and risk of periprosthetic fracture must be taken into account for patient education and appropriate prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 28 publications
0
43
0
Order By: Relevance
“…One topic that has not been frequently addressed in the past is osteoarthritis, which is becoming more of an issue especially in combination with haemophilic arthropathy. Joint replacements especially of the knee, elbow and ankle are now routinely performed in the larger haemophilia centres, and as patient live longer, redo joint surgery is more often encountered 12 …”
Section: Haemophilia and Ageingmentioning
confidence: 99%
“…One topic that has not been frequently addressed in the past is osteoarthritis, which is becoming more of an issue especially in combination with haemophilic arthropathy. Joint replacements especially of the knee, elbow and ankle are now routinely performed in the larger haemophilia centres, and as patient live longer, redo joint surgery is more often encountered 12 …”
Section: Haemophilia and Ageingmentioning
confidence: 99%
“…However, although some studies reported comparable outcomes of TKA in HA patients, limited data were available on the complications 8,9 . In order to have a more comprehensive understanding of the TKA safety in HA patients, it is necessary to identify the differences of complications between HA and other common articular diseases, such as osteoarthritis (OA) and rheumatoid arthritis (RA), which are the two dominated indicators of TKA.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies of HTO in HA, mobilization under anaesthesia was performed in 2 of 6 HTOs and 1 of 32 HTOs . The absence of postoperative stiffness in our study may be due to appropriate postoperative rehabilitation under careful supervision by the Korea Hemophilic Foundation …”
Section: Discussionmentioning
confidence: 66%
“…10 The absence of postoperative stiffness in our study may be due to appropriate postoperative rehabilitation under careful supervision by the Korea Hemophilic Foundation. 42 The present study has several limitations. First, this is a retrospective study without a control group and relatively short follow-up.…”
Section: Radiographic Evaluationmentioning
confidence: 83%